Symbolism and function: understanding the Linggi in Terengganu Traditional Perahu - Ngah, Nor Suraya Aini; Hasan, Ramly; Ngah, Che Muhamad Azmi; Abdullah, Mohd Yusof; Ngah, Nor Syamaliah (Faculty of Art and Design, 2025)
Terengganu's historical involvement in maritime activities has given rise to a diverse range of watercraft designs. Local researchers have conducted in-depth studies on the history, types and ornamentation of traditional boats called Perahu. However, types of Perahu based on its Linggi or stem head have yet to be explored. Due to limited written records on Terengganu traditional Perahu, the study employs a combination of interviews and observations to gather data. This study is carried out in line with the objective of realizing Sustainable Development Goal (SDG 11) 4: strengthening efforts to protect and safeguard the world's cultural and natural heritage. This study also promotes collaboration among governmental and private institutions, including the Ministry of Higher Education, Universiti Malaysia Kelantan and Universiti Teknologi Mara Seremban, Terengganu State Museum, and the Royal Terengganu Institute for Historical and Legal Studies, as part of the efforts to achieve Sustainable Development Goal (SDG 17). The objective of this study is to make a valuable contribution to the existing research by specifically focusing on types of Linggi; stem and stern post; steam head; and their designs. A qualitative approach is adopted, involving documents survey and observation on the collection of 17; 15 traditional fishing Perahu, 2 vessels namely Perahu Besar, and 1 prototype housed at the Terengganu State Museum. Through this investigation, the study classifies 3 types of Linggi based on its functions, 2 types based on construction method and 4 types of Linggi based on its design. The findings of this study have sparked further research on Terengganu Traditional Perahu, including investigations into the evolution of these traditional boats.